Expert System for Detecting Malaria Using the Certainty Factor Method - Seila Ria (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2023)
The expert system in this study is an expert system for diagnosing Malaria. The system provides consultation facilities to help users diagnose malaria. This identification process is carried out by selecting the symptoms experienced by the patient. The method used is the certainty factor method which provides a level of confidence from the results of the consultations carried out, with an easy design and in accordance with existing rules. So the program created is expected to represent an expert in diagnosing malaria. Utilization of databases to store the knowledge base of expert systems will make it easier to make knowledge addition facilities. With the addition of knowledge facilities